AN ANALYSIS OF GENDER DISPARITIES IN ACCESS TO HEALTH CARE IN KOLKATA ACROSS DIFFERENT LEVELS OF DEVELOPMENT - MOUMITA KUNDU,Dr. Arvind Kumar Singh (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2024)
This study examines the gender disparities in health care access in Kolkata, India, with a focus on how these disparities vary across high, medium, and low development zones within the city. Using a cross-sectional, mixed-methods approach, data were collected through structured surveys, interviews with health care providers, and secondary health records. The findings reveal that women, particularly in low development areas, face significant barriers to accessing health care, including financial constraints, lack of awareness, cultural restrictions, and inadequate infrastructure. Statistical analysis confirms that income, education, and area development level significantly influence women's access to health services. The study underscores the need for targeted interventions, including improved infrastructure, health education, and gender-sensitive policies, to promote equitable access to health care in urban settings like Kolkata.